Wellness through Sharing: The Trend of Routine Almsgiving in the Mental Health of Modern Muslims - Afrimaigus, Riko; Saadawy Mohammed, Ayman (Asian Journal of Muslim Philanthropy and Citizen Engagement, 2026)
The rise of digital philanthropy has fundamentally reshaped the practice of almsgiving (sadaqah), integrating it into the modern Muslim lifestyle as a component of holistic wellness. This study investigates the trend of routine, digitally-mediated almsgiving, arguing that it transcends its traditional role as a religious obligation to become a strategic practice for mental and spiritual well-being. Employing a qualitative library research methodology, this article systematically reviews and synthesizes scholarly literature to analyze the psychospiritual dimensions of this transformation. The findings demonstrate that regular giving functions as a potent spiritual coping mechanism, effectively alleviating urban stress and existential anxiety through neuropsychological rewards akin to the ‘helper’s high.’ Furthermore, the convergence of Islamic values, digital platforms, and psychological awareness fosters a novel ‘spiritual wellness economy.’ Within this paradigm, well-being is redefined: it is no longer anchored in material accumulation but is cultivated through social contribution and a sense of purposeful connectivity. This research concludes that routine digital sadaqah represents an epistemic shift in contemporary Islamic spirituality, effectively merging acts of worship with mental self-care. It signifies the emergence of a reflective wellness practice where true happiness is derived from sharing, offering a critical alternative to the individualistic pressures of digital capitalism. The study bridges discourses on Islamic philanthropy and positive psychology, providing a new framework for understanding faith-based wellness in the 21st century.